Expression of Concern Notice: Real Time Monitoring Research on Rehabilitation Effect of Artificial Intelligence Wearable Equipment on Track and Field Athletes - Wu, Bin (EAI Endorsed Transactions on Pervasive Health and Technology, 2026)
We, the publisher, are issuing an expression of concern about Bin Wu (2024) Real Time Monitoring Research on Rehabilitation Effect of Artificial Intelligence Wearable Equipment on Track and Field Athletes. https://doi.org/10.4108/eetpht.10.5150There is a concern over the integrity of the peer review review process and suspected manipulation of the editorial process. The investigation is ongoing and we advise scholars to exercise caution when referencing this manuscript.